The Influence of Product Display Product Display. Store Atmosphere, Service Quality, and Impulse Buying - Rio Hariyanto; Stephanie Astrid Ayu (Program Studi Manajemen Universitas Muslim Maros, 2023)
This study aims to determine the effect of product displays, store atmosphere, and service quality on impulse buying at Hokky Fruit Supermarket Merr Surabaya. The sample in this study amounted to 75 respondents. Methods of data analysis include: validity and reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. Based on the results of data research with SPSS Version 23, it was shown that all statement items for each variable in the questionnaire were declared valid with rcount > rtable of 0.227, all variables were declared reliable with cronbac'h alpha values ​​> 0.60. The results of the P-P Plot Normality Test show that the data used in this study are normally distributed. Multicollinearity test results showed no symptoms of multicollinearity between independent variables in the regression model with tolerance values ​​≥ 0.10 and VIF ≤ 10. Heteroscedasticity test results showed no symptoms of heteroscedasticity in the regression model because there was no clear pattern and there was a distribution of dots above and below the number 0 on the Y axis. The results of the multiple linear regression equation in this study are Y = 3.508 – 0.112 X1 – 0.172 X2 + 1.210 X3, the contribution of Product Display variables, Store Atmosphere, and Service Quality to Impulse Buying at Hokky Fruit Supermarket Merr Surabaya at 37.1% is included in the weak category. The results of the t test analysis show that Product Display and Store Atmosphere have no effect on Impulse Buying while Service Quality has a significant effect on Impulse Buying.